Effects of temperature on morphoagronomic performance, aroma gene expression and volatile profile of aromatic rice / Md. Zakaria Hossain Prodhan - Md. Zakaria , Hossain Prodhan (2016)
Production of aromatic rice with superior agronomic performance and excellent aroma is complicated due to the influences of environmental factors, cultural practice and genotypic condition. Among the environmental factors, the temperature is one of the most important factors that can affect growth, development, and production of aromatic rice as well as the quality of aroma performance. Therefore, selection of an appropriate growth stage and determination of a suitable temperature for proper expression of aroma gene is an important determinant for high-quality aromatic rice cultivation. The effects of the high day-night temperature, heat stress, and low-temperature stress on badh2 gene expression were investigated by previous researchers but a suitable temperature for proper expression of the badh2 gene and its relation with volatile compounds and the morphoagronomic performance of aromatic rice are still unrevealed. This study investigated the effects of three different temperatures (ambient or 28°C, 25°C and 20°C) on relative expression of badh2 gene, volatile profile, 2-Acetyl-1-pyrroline (2AP) concentration, phenotypic aroma expression as well as morphoagronomic performance of five aromatic and one non-aromatic rice genotype. The results indicated that the maximum down-regulation of badh2 gene (-18.31 fold), highest 2AP concentration (0.14 ± 0.02 ppm) and strong phenotypic aroma (score 4) were observed at 25°C temperature compared to ambient and 20°C temperature. The morphoagronomic traits were also varied on temperature condition where the 25°C facilitated better vegetative growth (Rato Basmati) and yield performance (E 13 genotype). Hence, the expression levels of the aroma gene and 2AP concentration were affected by temperature and regulated the phenotypic expression of an aroma at different growth stages in aromatic rice. This study is useful to develop a sustainable and suitable platform for production of high-quality aromatic rice.